Methodological Approach to Improve Energy Efficiency by Concentrating Operation Points an Electrical Transformer Maintenance Company - Toscano, Andres RodrÃguez; Castillo, Aurora Patricia Piñeres; Herazo, Julio Cesar Mojica; Restrepo, Rafael Ramirez (International Journal of Energy Economics and Policy, 2021)
In recent years, companies have developed strategies to improve the environment through the efficient use of their energy resources (RodrÃguez Toscano et al., 2019). This practice has been widely used in the goods manufacturing and transformation industry, but many opportunities for improvement remain in the services sector. In this context, this study offers a methodological and analytical approach to improve energy efficiency at a company that provides electric transformer maintenance services, based on performance of energy planning, analysis of concentration of operation points, and the implementation of operational and technological improvements to the processes. The results display total energy savings of 7% after implementation of the operational and technological improvements on only 23% of the company's energy-intensive equipment. Keywords: energy efficiency, technological improvement, electrical transformers JEL Classifications: I, L8 DOI: https://doi.org/10.32479/ijeep.11333